2021
DOI: 10.1021/acs.inorgchem.1c01376
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Alkali Metal Ion Recognition by Metalation of a Tris(saloph) Cryptand Having Benzene Rings at the Bridgeheads

Abstract: A cryptand derivative, H6L, which has three H2saloph arms connected by two benzene ring bridgeheads, was synthesized and converted into the trinuclear metallocryptand, LNi3. The nonmetalated host, H6L, was found to bind to alkali metal ions (Na+, K+, Rb+, Cs+; logK a = 3.37–6.67) in its well-defined cavity in DMSO/chloroform (1:9). The binding affinity was enhanced by 1–2 orders of magnitude upon the conversion into the metallocryptand, LNi3, which can be explained by the more polarized phenoxo groups in the [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 118 publications
0
11
0
Order By: Relevance
“…At first, the binding constant of ( R 6 )-LNi 3 with K + was determined by the competition experiment with 18-crown-6, which has a known binding constant of log K a = 4.98 with K + in CDCl 3 /DMSO- d 6 (9:1) (fig. S35) ( 57 ). The experiment revealed that ( R 6 )-LNi 3 can bind to K + 291 times stronger than 18-crown-6, which gave the binding constant of ( R 6 )-LNi 3 with K + to be log K a = 7.44.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At first, the binding constant of ( R 6 )-LNi 3 with K + was determined by the competition experiment with 18-crown-6, which has a known binding constant of log K a = 4.98 with K + in CDCl 3 /DMSO- d 6 (9:1) (fig. S35) ( 57 ). The experiment revealed that ( R 6 )-LNi 3 can bind to K + 291 times stronger than 18-crown-6, which gave the binding constant of ( R 6 )-LNi 3 with K + to be log K a = 7.44.…”
Section: Resultsmentioning
confidence: 99%
“…1C), because it has both a dynamic helical structure and a guest-binding site. This molecule can adopt a triple helical conformation in which the three metallosalen arms are twisted due to the rigid triphenylbenzene framework as seen in the previously reported tris(saloph) analog L 0 Ni 3 (H 2 saloph = N,N 0 -disalicylidene-ophenylenediamine) (46,57). This helical framework undergoes a dynamic chirality inversion on a timescale of minutes to hours, which can be easily monitored by spectroscopic techniques (46)(47)(48).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The helical complex [LCo 3 A 6 ](OTf) 3 was synthesized by the reaction of the corresponding free ligand ( 60 , 61 ) with cobalt(II) acetate under aerobic conditions in the presence of chiral amine A according to our previous report ( 54 ). The right-handed helix was dominant in a methanol solution, and the P / M diastereomeric ratio was 88:12 ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by using chiral amines on the same cage scaffold the helix to helix interconversion could also be controlled. [21] For all examples of salphen based cages discussed above, the salphen units are formed during the cage synthesis. [22] Due to the irreversible nature of the formation of the metal salphen units, it may be difficult to construct larger cages, by having this reaction as key-step.…”
Section: Introductionmentioning
confidence: 99%